Optimizing Village Bureaucracy Transformation: Gorontalo, Indonesia - Yanti Aneta; Sandi Prahara; Asna Aneta; Jamaluddin Ahmad (Indonesian Association for Public Administration, 2023)
This research analyzes bureaucratic transformation by optimizing village officials in Gorontalo Regency. Based on the research gap results, this study aims to analyze how bureaucratic transformation optimizes the role of village officials in providing public services. The academic interest of this research is to contribute new knowledge in the bureaucratic transformation field, especially through optimizing village officials. In addition, the practical importance is also quite significant, where this research can guide local governments and related stakeholders regarding strategies and concrete actions that can be taken to improve the quality of public services, bureaucratic efficiency, and responsiveness to community needs. This research uses simple descriptive statistics and is processed using the Nvivo 12 plus application. The community and local government want renewal or transformation in the bureaucratic structure of the village apparatus. The findings in the field are that the local government conducts competency mapping of village officials by conducting Computer Assisted Test (CAT) tests. The test results showed that of the 2089 participants who took part in the selection, only 179 people were ineligible, 50 people did not take the test, while those who passed the selection amounted to 1860. The transformation of the village bureaucracy was carried out through three steps, namely increasing the capacity of village officials, simplifying administrative procedures, and strengthening the supervisory system. The simplification of administrative procedures aims to reduce excessive bureaucracy and speed up public services. Strengthening the supervisory system also plays an important role in improving accountability and transparency.